1991
DOI: 10.1007/bf00037058
|View full text |Cite
|
Sign up to set email alerts
|

The tomato Cu,Zn superoxide dismutase genes are developmentally regulated and respond to light and stress

Abstract: The expression of the two Cu,Zn superoxide dismutase (SOD) genes of tomato was followed in different organs and plant developmental stages at the transcript and enzymatic activity levels. The cDNA clones used as probes code for the chloroplast Cu,Zn SOD (clone T1) and the cytosolic Cu,Zn SOD (clone P31). The two genes were found to display distinct expression patterns. While the T1 transcript was rare or absent from roots, stems and ripening fruits, the P31 transcript was very abundant in these organs. Shoot t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(86 citation statements)
references
References 34 publications
6
76
0
4
Order By: Relevance
“…It is possible that the high levels of Apxltranscript observed in response to other environmental stresses (Mittler and Zilinskas, 1992) might have also been restricted from interaction with polysomes. Such a mechanism for regulation of antioxidant enzymes may also apply to other systems in which similarly large differences were observed between stress-induced increase in steady-state transcript levels and increase in protein and/or activity (Bowler et a/., 1989;Perl-Treves and Galun, 1991;Williamson and Scandalios, 1992).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that the high levels of Apxltranscript observed in response to other environmental stresses (Mittler and Zilinskas, 1992) might have also been restricted from interaction with polysomes. Such a mechanism for regulation of antioxidant enzymes may also apply to other systems in which similarly large differences were observed between stress-induced increase in steady-state transcript levels and increase in protein and/or activity (Bowler et a/., 1989;Perl-Treves and Galun, 1991;Williamson and Scandalios, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Drought stress was chosen for two reasons: (i) episodes of water deficiency are among the most common environmental stresses encountered by plants during their growth period; and (ii) drought stress is believed to be accompanied by the production of activated oxygen species and has been reported to result in increased activity of antioxidant enzymes (Mittler and Zilinskas, 1992;Perl-Treves and Galun, 1991;Smirnoff and Colombe, 1988;Tanaka eta/., 1990). Drought stress, as indicated by a decrease in leaf water potential and stomatal closure (especially at D2 and D3, Figure I ) , resulted in an increase in cytosolic APX and Cu/Zn-SOD gene expression and in an increase in catalase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although Cu/Zn-SOD II did not respond to Mn toxicity, one might not rule out a direct effect of excess Mn in the chloroplast of mature leaves. Even with oxidative stress caused by paraquat, which is believed to target the chloroplast, increases in cytosolic and plastidic Cu/Zn-SOD have been reported (Perl-Treves and Galun, 1991). Aono et al (1991) showed that transformed plants expressing bacterial GR in the cytosol were more resistant to paraquat than untransformed plants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reaction to drought was clone, leaf age-and drought intensity-dependant: SOD and catalase activities were stimulated during severe drought in the mature leaves of the tolerant clone 'Dorskamp', while peroxidase seemed favored during mild drought in the expanding leaves of the more susceptible clone 'Luisa_Avanzo'. Stimulation of the antioxidant enzymatic activities of the Halliwell-Asada pathway has commonly been observed in response to drought [14,16]. Nevertheless, the implication of these enzymes under drought conditions has been shown to be diverse according to species and/or to drought intensity [18].…”
Section: Resultsmentioning
confidence: 99%